Alumina powder
Patent Information
- Application Number
- JP2023563748
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-11-26
- Filing Date
- 2022-11-25
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-11-25
Smart Images

Figure 0007943866000001 
Figure 0007943866000002 
Figure 0007943866000003
Abstract
Description
[Technical Field]
[0001] This disclosure relates to alumina powder, and more particularly to alumina powder that can be used to produce sintered bodies with excellent plasma resistance. [Background technology]
[0002] In the semiconductor component manufacturing process, an oxide insulating film formed on a Si wafer is partially removed using corrosive gas and plasma to form a circuit pattern. At this time, components of the semiconductor manufacturing equipment (e.g., electrostatic chucks) are also exposed to the corrosive gas and plasma. As a result, particles on the order of several micrometers are generated from the components, which may cause the circuit formed on the Si wafer to break (part of the circuit is not formed due to particle deposition). Therefore, components with excellent plasma resistance are being investigated to suppress particle generation (for example, Non-Patent Literature 1). Non-Patent Literature 1 describes that ceramic films fabricated by the AD (aerosol deposition) method have superior plasma resistance compared to conventional ceramic sintered bodies. [Prior art documents] [Non-patent literature]
[0003] [Non-Patent Document 1] "Development of low-dusting materials with excellent plasma resistance," Kiyohara et al., Ceramics, 50 (2015) No. 6, The Ceramic Society of Japan [Overview of the Initiative] [Problems that the invention aims to solve]
[0004] The AD method is an excellent technique for obtaining dense ceramic films without heating, but it has challenges in terms of continuous production due to the need for chamber equipment and exhaust. The inventors of the present invention have diligently investigated the conditions for alumina powder to produce ceramic sintered bodies, particularly alumina sintered bodies, with excellent plasma resistance, using existing firing technologies. Since it is necessary to use appropriate alumina powder to obtain such alumina sintered bodies, the embodiments of the present invention aim to provide alumina powder that can produce alumina sintered bodies with excellent plasma resistance. [Means for solving the problem]
[0005] One aspect of the present invention is: This alumina powder has a relative standard deviation of 0.25 to 0.80 for its volume-based crystallite size distribution, determined by analyzing X-ray diffraction peaks using the fundamental parameter method.
[0006] Aspect 2 of the present invention is The alumina powder according to embodiment 1, wherein the average roundness of the alumina particles constituting the alumina powder is 0.71 to 0.86.
[0007] Aspect 3 of the present invention is The alumina powder according to embodiment 1 or 2, wherein the volume-based crystallite size is 650 to 1400 Å. [Effects of the Invention]
[0008] By using the alumina powder according to the embodiment of the present invention, an alumina sintered body with excellent plasma resistance can be manufactured. [Modes for carrying out the invention]
[0009] The inventors of this invention have found that the selection of alumina powder, the raw material, is crucial for improving the plasma resistance of alumina sintered bodies. Based on this finding, further intensive research has led to the discovery that the plasma resistance of alumina sintered bodies can be improved by controlling the crystallite size of the alumina powder, particularly the relative standard deviation of the volume-based crystallite size distribution (known as "distribution RSD," sometimes simply referred to as "distribution RSD"), to 0.25-0.80. Based on this discovery, the inventors have perfected an alumina powder capable of producing alumina sintered bodies with excellent plasma resistance.
[0010] The alumina powder according to an embodiment of the present invention will be described.
[0011] The alumina powder according to this embodiment has a relative standard deviation (distribution RSD) of 0.25 to 0.80 of the volume-based crystallite size distribution, which is determined by analyzing the X-ray diffraction peaks using the fundamental parameter (FP) method.
[0012] The Fundamental Parameter (FP) method allows for the determination of the distribution RSD based on the X-ray diffraction pattern. This RSD determination using the FP method is performed using analysis software. For example, commercially available analysis software (SmartLab Studio II, integrated powder X-ray analysis software from Rigaku Corporation) is used to analyze the diffraction profile obtained from powder X-ray diffraction measurements. The analysis conditions (peak profiling settings) are set as follows: Peak shape: FP (Fundamental Parameter) method, Crystallite size distribution type: Log-normal distribution.
[0013] Powder X-ray diffraction of alumina powder can be performed using a commercially available X-ray diffractometer (e.g., SmartLab, manufactured by Rigaku Corporation). While the X-ray source is not limited, CuKα can be used. The measurement range for the diffraction angle 2θ is, for example, 10° to 90°. As the X-ray diffraction peak used for analysis, for example, in the case of α-alumina, the peak of the (113) plane on the high angle side with high detection intensity (when the X-ray source is CuKα, the peak at 2θ = 43.0±1°) is used.
[0014] Alumina powder having a distribution RSD in the range of 0.25 to 0.80 determined by the above method is suitable for producing an alumina sintered body having excellent plasma resistance. Although the reason is not clear, the fact that the distribution RSD is 0.25 to 0.80 means that the volume-based crystallite diameters of the alumina powder are relatively uniform. It is considered that the uniform volume-based crystallite diameters contribute to the improvement of plasma resistance. Incidentally, in the present specification, the volume-based crystallite diameter may be referred to as "volume average diameter" or "crystallite diameter".
[0015] Note that the smaller the distribution RSD, the more uniform the crystallite diameter, but since it is not always easy to make the distribution RSD smaller than 0.25, the lower limit is set to 0.25. The distribution RSD is preferably 0.27 to 0.72, more preferably 0.30 to 0.64, and particularly preferably 0.34 to 0.57.
[0016] The average circularity of the alumina particles constituting the alumina powder is preferably 0.71 to 0.86. Within this range, the plasma resistance can be further improved. The average circularity of the alumina particles is more preferably 0.75 to 0.85, and particularly preferably 0.79 to 0.85.
[0017] The average circularity of alumina particles is calculated by the following procedure. An SEM image of the alumina particles is acquired. The alumina particles are fixed on a carbon tape. The SEM image can be obtained by acquiring at a predetermined acceleration voltage with a scanning electron microscope (for example, scanning electron microscope "S-5500" manufactured by Hitachi High-Technologies Corporation). The acquired SEM images are binarized using image processing software (for example, the free software ImageJ (https: / / fiji.sc / )) to calculate the area of the alumina particles enclosed by the contour (the "area" in equation (1)) and the major axis diameter of the ellipse when the alumina particles are approximated as an ellipse (the "major axis diameter" in equation (1)). The roundness of a single alumina particle is calculated using the following formula (1). The roundness of a single alumina particle = 4 × area / [π × (major axis diameter)] 2 ]···(1) For at least 25 alumina particles, calculate the roundness of each individual particle, and define the average of these values as the "average roundness of the alumina particles."
[0018] As can be seen from equation (1), the closer the "roundness of a single alumina particle" is to 1, the closer the shape of that alumina particle in the SEM image will be to a perfect circle. Therefore, the closer the average roundness of the alumina particles is to 1, the closer the shape of the alumina particles constituting the alumina powder will be to a perfect circle in the SEM image.
[0019] The alumina powder preferably has a volume-based crystallite size of 650 to 1400 Å. Within this range, plasma resistance can be further improved. The crystallite size, like the distributed RSD, is determined by analyzing the powder X-ray diffraction profile using commercially available analysis software (for example, Rigaku Corporation's integrated powder X-ray analysis software, SmartLab Studio II). The crystallite size is more preferably 800 to 1350 Å, even more preferably 820 to 1350 Å, and particularly preferably 820 to 950 Å.
[0020] From the viewpoint of obtaining excellent plasma resistance, the alumina powder mainly contains α-alumina, and may also be a mixture containing one or more of γ-alumina, η-alumina, θ-alumina, δ-alumina, boehmite, and pseudo-boehmite. The α-alumina content in the alumina powder is preferably 90% by weight or more, more preferably 99% by weight or more, and most preferably 99.9% by weight or more.
[0021] Alumina powder consists substantially of alumina, but may contain unavoidable impurities such as Fe, Si, and / or Na, which are introduced depending on the raw materials, materials, or manufacturing equipment. These unavoidable impurities may be present as long as they do not significantly degrade the plasma resistance of the alumina material, and generally, the acceptable amount is 100 ppm or less in total. The total content is preferably 10 ppm or less. The content of Fe, Si, Na, etc., can be measured by emission spectroscopy.
[0022] An example of a manufacturing method that can produce the alumina powder of this embodiment is shown.
[0023] The method for producing alumina powder according to the embodiment is: A step to prepare a seed crystal slurry in which seed crystals are dispersed, The process involves mixing the seed crystal slurry with aluminum alkoxide to obtain an aluminum hydroxide slurry. The process includes the step of drying and calcining the aluminum hydroxide slurry to obtain alumina powder. Furthermore, the process may include a step of grinding the obtained alumina powder. The process of obtaining an aluminum hydroxide slurry may include a step of chelating an aluminum alkoxide prior to that step.
[0024] Each step will be described in detail.
[0025] [1. Steps to prepare seed crystal slurry] Alumina particles (the raw material for seed crystals) are dispersed in water and then wet-milled using a ball mill. Afterward, the mixture is centrifuged using a cooled centrifuge (e.g., Himac CR7N) to remove the precipitate. This yields a seed crystal slurry in which the seed crystals are dispersed.
[0026] The seed crystal is preferably α-alumina. By using α-alumina seed crystals, the α-conversion of alumina can be promoted at low temperatures during the firing process described later. The seed crystals are preferably small in size, and typically those with a particle size of 0.01 μm to 0.2 μm are used.
[0027] The BET specific surface area of the seed crystal contributes to the crystallite size of the final alumina powder. To make the distribution RSD of the alumina powder within the range of the embodiment (0.25 to 0.80) and / or the crystallite size within the preferred range (650 to 1400 Å), the BET specific surface area of the seed crystal is preferably 30 m². 2 / g or more, more preferably 40m 2 / g or more, more preferably 50m 2 / g or more, particularly preferably 70m 2 Make it 1g or more. The BET specific surface area is determined by the nitrogen adsorption single-point method, in accordance with the method specified in JIS-Z-8830:2013 "Method for measuring the specific surface area of powders (solids) by gas adsorption".
[0028] The seed crystal content in the seed crystal slurry is not particularly limited, as long as the resulting seed crystal slurry has appropriate fluidity. For example, the seed crystal content in the seed crystal slurry is 5% to 40% by mass.
[0029] [2. Step of chelating aluminum alkoxide] Optionally, the process may include a step of chelating the alumina alkoxide. In this step, the aluminum alkoxide is chelated with a chelating agent. Chelating causes bulky ligands to coordinate and create steric hindrance, thus more effectively suppressing the condensation reaction of the aluminum alkoxide that occurs during hydrolysis, as described later, compared to unchelated aluminum alkoxide. Suppressing the condensation reaction makes it easier to obtain fine aluminum hydroxide particles.
[0030] Examples of aluminum alkoxides that can be used include aluminum ethoxide, aluminum n-propoxide, aluminum isopropoxide, aluminum n-butoxide, aluminum sec-butoxide, and aluminum t-butoxide.
[0031] Examples of chelating agents that can be used include ethyl acetoethyl, triethanolamine (TEA), and ethylenediamine (EDA).
[0032] [3. A step of mixing the seed crystal slurry with the (optionally chelated) aluminum alkoxide to obtain an aluminum hydroxide slurry.] Seed crystal slurry and (optionally chelated) aluminum alkoxide are continuously supplied to a stirrer and mixed. By rapidly rotating and shearing this mixture with the stirrer, the water in the seed crystal slurry and the aluminum alkoxide undergo a hydrolysis reaction, yielding a slurry (aluminum hydroxide slurry) containing aluminum hydroxide particles, which are the hydrolysis products.
[0033] The supply amounts of seed crystal slurry and (optionally chelated) aluminum alkoxide are preferably controlled to ensure an appropriate seed crystal content in the mixture. In particular, the seed crystal content contributes to the crystallite size of the final alumina powder. To make the distribution RSD of the alumina powder within the range of the embodiment (0.25 to 0.80) and / or the crystallite size within a preferred range (650 to 1400 Å), the preferred seed crystal content is such that, in terms of oxides of the metal components in the mixture (aluminum components contained in aluminum alkoxide and seed crystals), the aluminum component in the seed crystals is 1 part by mass or more, preferably 2 parts by mass or more, and 50 parts by mass or less, preferably 40 parts by mass or less, and particularly preferably 30 parts by mass or less, per 100 parts by mass of the total amount of aluminum components in the mixture.
[0034] Furthermore, it is preferable to control the supply amounts of seed crystal slurry and (optionally chelated) aluminum alkoxide so that the mixing ratio of (water contained in seed crystal slurry) / ((optionally chelated) aluminum alkoxide) is in the range of approximately 1.5 to approximately 6.0 in molar ratio.
[0035] One of the features of this process is high-speed rotary shear stirring of the mixture. In this specification, "high-speed rotary shear stirring" refers to stirring performed by mechanical energy such as shear force, pressure fluctuations, cavitation, impact force, and potential core generated between the turbine (rotor) and the stator (screen) when the clearance between the turbine (rotor) and the stator (screen) is small (e.g., 2 mm or less) and the turbine (rotor) is rotating at high speed (e.g., peripheral speed of approximately 1 m / sec to approximately 40 m / sec).
[0036] Examples of agitators capable of performing such high-speed rotational shear stirring include the TK Homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.), Creamix (manufactured by M-Technic Co., Ltd.), Polytron Homogenizer, Megatron Homogenizer (KINEMATICA), and Supraton (manufactured by Tsukishima Kikai Co., Ltd.).
[0037] In high-speed rotary shear stirring, the turbine (rotor) rotation speed is set to 3000 rpm to 21500 rpm, preferably 8000 rpm to 15000 rpm, for example, 10000 rpm. When the rotation speed is within the above range, the two liquids, water in the seed crystal slurry and (chelated) aluminum alkoxide, can be thoroughly mixed, and the aggregation of aluminum hydroxide in the resulting aluminum hydroxide slurry can be suppressed. As a result, an aluminum hydroxide slurry containing fine aluminum hydroxide particles can be obtained. Furthermore, the seed crystals can be uniformly dispersed in the aluminum hydroxide slurry.
[0038] Furthermore, the hydrolysis of aluminum alkoxide can be carried out using a continuous reactor. Applicable continuous reactors include tank-type and pipeline-type reactors. In the tank-type reactor, seed crystal slurry and (optionally chelated) aluminum alkoxide are continuously supplied to a tank equipped with a high-speed rotating shear agitator, and the hydrolysis of aluminum alkoxide (and the generation of aluminum hydroxide particles) is carried out while continuously discharging the same amount of liquid as supplied. In the pipeline-type reactor, seed crystal slurry and (optionally chelated) aluminum alkoxide are continuously supplied to a high-speed rotating shear agitator incorporated into the line. Compared to batch-type reactors, these continuous reactors offer extremely high productivity and uniform conditions for the generation of aluminum hydroxide particles, resulting in an aluminum hydroxide slurry containing aluminum hydroxide with a uniform particle size distribution and no coarse aggregated particles.
[0039] [4. Step of drying and calcining the aluminum hydroxide slurry to obtain alumina powder] Alumina powder is obtained by drying an aluminum hydroxide slurry by a known method and then calcining the resulting aluminum hydroxide in a calcination furnace. Firing is usually carried out at 800°C or higher, preferably 900°C or higher, usually 1000°C or lower, preferably 980°C or lower, and even more preferably 960°C or lower. Above 1000°C, it is difficult to obtain fine alumina powder. Also, below 800°C, the α-phase content in the alumina powder tends to be low.
[0040] The calcination may be carried out in the atmosphere or in an inert gas such as nitrogen or argon, and it is effective to maintain a high water vapor partial pressure in the atmosphere during calcination. In particular, if the process does not include the step of chelating aluminum alkoxide, calcining in an atmosphere with a high water vapor partial pressure (i.e., a high dew point atmosphere) allows the α phase to be obtained at a low calcination temperature. If the process includes the step of chelating aluminum alkoxide, the α phase can be obtained in an atmosphere with a low water vapor partial pressure (i.e., a low dew point atmosphere) and at a low calcination temperature.
[0041] Firing can be carried out using conventional firing furnaces such as tubular electric furnaces, box electric furnaces, tunnel furnaces, far-infrared furnaces, microwave heating furnaces, shaft furnaces, reverberatory furnaces, rotary furnaces, roller hearth furnaces, and gas (LNG, LPG) furnaces. Firing may be carried out in batches or continuously. It may also be carried out in a static or fluidized bed system.
[0042] To control the dew point during firing, if an electric furnace or tubular furnace is used as the firing furnace, for example, spraying water into the dry air introduced into the furnace or introducing steam into the furnace are effective methods. If a gas combustion furnace is used as the firing furnace, introducing moisture generated by burning fuels such as gas or petroleum into the furnace is effective, and further introducing steam makes it even more effective.
[0043] The dew point can be determined using a conversion table with the amount of water vapor, or by a calculation formula using water vapor pressure. Water vapor pressure and water vapor amount (absolute humidity) can be determined from the saturated water vapor pressure or saturated water vapor amount and relative humidity, respectively. Saturated water vapor pressure can be calculated using Tetens' formula.
[0044] If the process does not include a step of chelating aluminum alkoxide, it is preferable to control the dew point in the furnace to be 30°C or higher, more preferably to control it to be 40°C or higher, and particularly preferably to control it to be 50°C or higher.
[0045] In this way, alumina powder with a distribution RSD of 0.25 to 0.80 can be obtained. Furthermore, by controlling the BET specific surface area of the seed crystal and / or the seed crystal content in the aluminum hydroxide slurry, alumina powder with a crystallite size of 650 to 1400 Å can be obtained.
[0046] [5. Step of grinding the obtained alumina powder] Although alumina powder according to the embodiment of the present invention can be obtained by the manufacturing method described above, the alumina powder may be further pulverized. For pulverizing the alumina powder, a media pulverizer such as a vibratory mill, ball mill, or jet mill can be used. The pulverized alumina powder may also be classified. Normally, alumina powder for sintering is crushed to adjust the particle size before molding and sintering. However, the alumina powder according to this embodiment tends to have a larger distributed RSD when crushed, so it is preferable not to crush it in order to keep the distributed RSD low.
[0047] In the embodiments described, the alumina powder of this disclosure has been described as a suitable raw material for manufacturing components of semiconductor manufacturing equipment such as electrostatic chucks. However, it can also be used as a raw material for coatings, thermal spray films, oxide sintered bodies, composite oxide sintered bodies, bearings, ceramic beads, fillers for semiconductor encapsulating resins, heat dissipation fillers, insulating fillers, light reflectors, light scattering materials, blasting materials, abrasive grains, biomaterials, dental materials, and the like. [Examples]
[0048] (Example 1) The method for preparing the alumina powder sample (Sample No. 1) according to Example 1 will be described below.
[0049] [Preparation of seed crystal (α-alumina) slurry] Alumina particles (the raw material for seed crystals) were dispersed in water and then wet-milled using a ball mill. Subsequently, the mixture was centrifuged for 30 minutes at 4000 rpm using a cooled centrifuge (himac CR7N) to remove the precipitate. This yielded a seed crystal slurry in which the seed crystals were dispersed. Furthermore, the BET specific surface area of the seed crystals in the obtained seed crystal slurry was measured. First, the water in the seed crystal slurry was evaporated to obtain seed crystals, and the BET specific surface area was determined by the nitrogen adsorption single-point method according to the method specified in JIS-Z-8830:2013 "Method for measuring the specific surface area of powders (solids) by gas adsorption". The measurement results of the BET specific surface area of the seed crystals are shown in Table 1.
[0050] [Preparation of chelated aluminum isopropoxide] Aluminum isopropoxide was chelated to prepare chelated aluminum isopropoxide (indicated as "yes" in "Presence or absence of chelation" in Table 1). By mixing aluminum isopropoxide and ethyl acetoethyl (chelating agent) in a molar ratio of 100:3, 3 mol% chelated aluminum isopropoxide was obtained.
[0051] [Production of α-alumina powder] Chelated aluminum isopropoxide and seed crystal slurry were mixed and hydrolyzed at a rotation speed of 10,000 rpm using a precision emulsification and dispersion machine, Creamix CLM-2.2S (manufactured by M-Technique Co., Ltd.). This yielded an aluminum hydroxide slurry. The mixing ratio of chelated aluminum isopropoxide to seed crystal slurry was determined so that the ratio of (water contained in seed crystal slurry) / (chelated aluminum isopropoxide) was 2.7 / 1 (molar ratio). With this mixing ratio, the aluminum hydroxide slurry contains 2 parts by mass of aluminum components from the seed crystal for every 100 parts by mass of the total amount of (chelated) aluminum isopropoxide and aluminum components from the seed crystal, in terms of oxides of the metal components. The content (parts by mass) of each aluminum component was calculated assuming that all of the aluminum isopropoxide used would be converted into alumina.
[0052] The obtained aluminum hydroxide slurry was dried at 150°C to obtain aluminum hydroxide particles, which were then placed in an alumina crucible and fired in a box-type electric furnace. The firing conditions were as follows: the temperature was raised to 985°C at a heating rate of 200°C / hour, and the temperature was maintained at that temperature for 4 hours.
[0053] (Examples 2-6) In the samples of Examples 2 and 3 (Samples No. 2 and 3), the BET specific surface area of the seed crystal, the number of seed crystals added, and the calcination temperature of the aluminum hydroxide particles were changed, as shown in Table 1. In the samples of Examples 4, 5, and 6 (Samples No. 4, 5, and 6), the BET specific surface area of the seed crystal, the number of seed crystals added, and the calcination temperature of the aluminum hydroxide particles were changed as shown in Table 1, and further grinding was performed using a ball mill after calcination.
[0054] (Examples 7-12) In the samples of Examples 7, 8, and 9 (samples No. 12, 13, and 14), aluminum isopropoxide was used without chelation (indicated as "none" in Table 1 under "Presence or Absence of Chelation"). Furthermore, as shown in Table 1, the BET specific surface area of the seed crystal, the number of seed crystals added, and the calcination temperature of the aluminum hydroxide particles were varied. A gas furnace was used instead of a box-type electric furnace for calcining the aluminum hydroxide particles. In the samples of Examples 10, 11, and 12 (Samples No. 15, 16, and 17), as shown in Table 1, aluminum isopropoxide was used without chelation, and the BET specific surface area of the seed crystals, the number of seed crystals added, and the calcination temperature of the aluminum hydroxide particles were changed. The samples were calcined in a gas furnace, and then further ground in a ball mill after calcination.
[0055] (Comparative Examples 1-5) In Comparative Example 1 (Sample No. 7), as shown in Table 1, no seed crystals were added, the calcination temperature of the aluminum hydroxide particles was changed, and further grinding was performed using a ball mill after calcination. The samples for Comparative Examples 2-5 (Samples No. 8-11) are commercially available high-purity alumina manufactured by Sumitomo Chemical, as shown in Table 2.
[0056] Table 1 shows the manufacturing conditions for each sample in Examples 1-12 and Comparative Example 1, Table 2 shows the types of samples in Comparative Examples 2-5, and Tables 3-4 show the measurement and calculation results for each sample in Examples 1-12 and Comparative Examples 1-5. In Table 3, underlined values indicate that they fall outside the scope or preferred range of the embodiments of the present invention.
[0057] [Table 1]
[0058] [Table 2]
[0059] [Table 3]
[0060] [Calculation of volume-based crystallite size (volume-average diameter) and the relative standard deviation (distribution RSD) of the volume-based crystallite size distribution] For α-alumina powder, the volume-based crystallite size (volume-average diameter) and the relative standard deviation of the volume-based crystallite size distribution (distribution RSD) were determined using the fission product (FP) method. Powder X-ray diffraction measurements were performed on α-alumina powder using CuKα as the radiation source, within the measurement range of diffraction angle 2θ = 10° to 90°. The X-ray diffractometer used was a SmartLab manufactured by Rigaku Corporation. The diffraction profiles obtained from the powder X-ray diffraction measurements were analyzed using analysis software (integrated powder X-ray analysis software SmartLab Studio II, manufactured by Rigaku Corporation). The analysis conditions (peak profiling settings) were set to peak shape: FP (Fundamental Parameter) method, and crystallite size distribution type: log-normal distribution. By selecting diffraction peaks within the range of 2θ = 43.0 ± 1° corresponding to the (113) plane of α-alumina and analyzing them, the relative standard deviation (distribution RSD) of the volume-based crystallite size distribution was calculated.
[0061] Furthermore, using the crystallite size distribution view of the analysis software, a crystallite size distribution function curve was plotted with the volume-average diameter on the x-axis and the probability density function of crystallites against crystallite size on the y-axis, with a total area of 1. Table 3 shows the volume-average diameter and distribution RSD values for each sample.
[0062] [Manufacturing of molded sintered bodies] A molded sintered body was prepared using α-alumina powder. An appropriate amount of α-alumina powder was uniaxially pressed at 30 MPa using a φ20 mm mold, and then subjected to a hydrostatic press at 98 MPa to obtain a molded body with a surface dimension of φ20 mm and a thickness of 5-10 mm. The molded body was placed in an alumina crucible and placed in a box-type electric furnace, and the temperature was raised to a sintering temperature of 1450°C at a heating rate of 200°C / hour. The molded body was sintered by holding it at this temperature for 2 hours to obtain a molded sintered body. The surface of the obtained molded sintered body was polished to prepare a sintered body sample for measurement.
[0063] [Plasma resistance evaluation] After exposing the sintered body sample to plasma, its surface roughness was evaluated to assess its plasma resistance. After masking one half of the surface of the sintered body sample with a tape, the sample was placed in a plasma etching apparatus (manufactured by Samco: RIE-400iPBT). The surface of the sintered body sample was exposed to plasma in a mixed atmosphere gas of CF4, SF6 and Ar at an output of 1 kW for 5 hours. Regarding the surface roughness of the plasma-exposed surface (the surface exposed to plasma), a laser microscope (manufactured by Keyence: VK-X3000) was used to measure the surface roughness Sa of the surface under the conditions of a lens magnification of 50x, a pitch of 0.1 μm, and a measurement range of 214.5 μm (768 pix) in the vertical direction and 286.1 μm (1024 pix) in the horizontal direction. The measurement was performed at 3 different locations on each sample, and the average value thereof was taken as the surface roughness Sa of the plasma-exposed surface EX . In addition, the surface after the tape was peeled off (referred to as "masked surface") was also measured for its surface roughness Sa under the same measurement range and measurement conditions. The measurement was performed at 3 different locations on each sample, and the average value thereof was taken as the surface roughness Sa of the masked surface MK .
[0064] The surface roughness Sa of the plasma-exposed surface EX and the surface roughness Sa of the masked surface MK The difference ΔSa (ΔSa = Sa EX - Sa MK ) was determined. The surface roughness Sa of the plasma-exposed surface EX , the surface roughness Sa of the masked surface MK , and their difference ΔSa are shown in Table 4.
[0065] [Table 4]
[0066] The samples of Examples 1 to 12 (Sample Nos. 1 to 6, 12 to 17) were alumina powders produced by adding seed crystals having appropriate physical properties (particularly BET specific surface area) in an appropriate amount. Therefore, the distribution RSD of the obtained alumina powder was within the range of the embodiment. The molded sintered bodies produced using these alumina powders were found to have a small difference ΔSa between the surface roughness Sa of the plasma-exposed surface EX and the surface roughness Sa of the masked surface MK , and to have high plasma resistance.
[0067] On the other hand, the sample in Comparative Example 1 (Sample No. 7) was alumina powder prepared without the addition of seed crystals. Therefore, the distribution RSD of the obtained alumina powder was outside the scope of the embodiment. Furthermore, the samples in Comparative Examples 2-5 (Samples No. 8-11) were commercially available alumina powders prepared for comparison. The distribution RSD of these alumina powders was outside the scope of the embodiment. The molded sintered body made using these alumina powders has a surface roughness of Sa on the plasma-exposed surface. EX and the surface roughness of the mask surface Sa MK The large difference ΔSa indicates that the plasma properties are inferior.
[0068] This application is based on a Japanese patent application, Japanese Patent Application No. 2021-192363, filed on November 26, 2021. Japanese Patent Application No. 2021-192363 is incorporated herein by reference.
Claims
1. Alumina powder having a relative standard deviation of volume-based crystallite size distribution of 0.25 to 0.80, obtained by analyzing the X-ray diffraction peak using analysis software (integrated powder X-ray analysis software SmartLab Studio II, manufactured by Rigaku Corporation) with the fundamental parameter method (analysis conditions (peak profiling settings) being: peak shape: FP (Fundamental Parameter) method, crystallite size distribution type: log-normal distribution).
2. The alumina powder according to claim 1, wherein the average roundness of the alumina particles constituting the alumina powder is 0.71 to 0.
86.
3. The alumina powder according to claim 1 or 2, wherein the volume-based crystallite size is 650 to 1400 Å.
Citation Information
Patent Citations
METHOD OF FINE PARTICULATE alpha-ALUMINA
JP2005001984A
METHOD OF FINE PARTICULATE alpha-ALUMINA
JP2005001985A
Method for producing alpha-alumina particulate
JP2005097075A
Method for producing particulate alpha-alumina
JP2007161560A
Precipitated alumina and its preparation method
JP2017523952A
